(untitled) (The South East European Journal of Economics and Business, 2025)
This study investigates the impact of the five main risks (production, market, financial, legal compliance, and human resources) along with risk analysis, farmer experience, and farm size on farm income. The research is based on primary data collection consisting of 300 valid questionnaires. The respondents were randomly selected, and the interviews were conducted face-to-face. Explanatory (principal component analysis) and inferential statistical (regression analysis) approaches are employed to test the formulated hypotheses. The results showed that risk analysis, experience, and farm size significantly affect farm income. Additionally, legal risk and production risk were significant and influenced farm income, whereas financial risk, market risk, and human resources risk did not. The findings of the research assist farmers, field researchers, policymakers at local and central levels, and other stakeholders such as clients, suppliers, and consumers. This guides farmers in effective risk management and helps government institutions in drafting supportive policies for the sustainable development of agriculture.